Association between CYP2A13 Polymorphisms and Lung Cancer Risk : A Systematic Review and Meta-Analysis of Case–Control Studies - Voon, Fui Ling; Edmund Sim, Ui Hang (Thieme Medical and Scientific Publishers Pvt. Ltd., 2025)
Objectives